PENGARUH TERAPI KELOMPOK TERAPEUTIK TERHADAP KEMAMPUAN IBU DALAM MENSTIMULASI PERKEMBANGAN PSIKOSOSIAL OTONOMI DAN KECEMASAN BERPISAH PADA KANAK-KANAKDI POSYANDU MELATI RW II KELURAHAN TLOGO MAS KOTA MALANG - Lilik Supriati**, Esti Widiani* Ahsan** (Universitas Muhammadiyah Jember, 2015)
In particular health problems of psychosocial development into one of the issues that need to be considered, so that the necessary efforts to improve health throughout the life span. Critical period which requires stimulation among which toddler. The aim in this study was to obtain an overview of Effect of Therapeutic Group on Mother Ability to Stimulate of Psychosocial Development Autonomy and Separation Anxiety OnToddler In Posyandu RW II Tlogomas Malang. The research design is quasi-experimental pre-post test with control group. The technique used for sampling in this study is simple random sampling with 25 samples obtained for the treatment group and 26 samples for the control group. The results showed an increase in the mother's ability to stimulate the development of autonomy and separation anxiety in the group receiving therapeutic group was significantly higher (p value <0.05) compared with the control group. This therapy is recommended to be done on mental health services for mothers who have children ages 18 months -3 years.